Does tourism specialization lead to regional economic development? Empirical evidence from Mexico - Prelorenzo , Diana (2021)
A key driver of international economic growth, the tourism industry is described as a great provider of revenue, foreign currencies and jobs among other benefits. Indeed, international tourist arrivals had a dynamic continuous growth reaching 1,460 million arrivals (2019) representing nearly 10% of global Gross Domestic Product (GDP). It also provides 1 in 10 jobs for a total of some 330 million jobs worldwide . Those ultimate years, Mexico became a top visited country with 45 million international tourists (UNWTO, 2021). Even with the pandemic, Mexico passed from the 7th place to the 3th in 2020 due to the flexibility to enter the country. Indeed, since the seventies, mexican policies have implemented various projects to develop international tourism. One of the most known is the region of Cancun developed by the Integrally Planned Centers (IPC), which has become a major touristic city as travel and tourism sector (including direct, indirect and induced impacts) accounted for 40.3% of the employment and 46.8% of the participation in the state's GDP (WTTC, 2019). Nevertheless, the mexican tourism strategy to develop its competitive advantages is based on low cost 3S (Sea, Sun, Sand) offers with mainly “all inclusive” packages. Besides, five destinations represent more than 90% of the total of international aerial arrivals (Sectur, 2021). This study aims to analyse the degree of specialization of the Mexican states to evaluate the regional economic development linked to the tourism industry and determine the relationship between tourism specialization and regional economic development